2009
DOI: 10.1039/b901209e
|View full text |Cite
|
Sign up to set email alerts
|

Shedding light on water structure at air–aqueous interfaces: ions, lipids, and hydration

Abstract: An account is given of the current state of understanding of aqueous salt, acid, and lipid/water surfaces, interfacial depth, and molecular organization within the air-solution interfacial region. Water structure, hydration, surface propensity of solutes, and surface organization are discussed. In this perspective, vibrational sum frequency generation spectroscopic studies of aqueous surfaces are interpreted. Comment on future directions within the field of aqueous surface structure is provided.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
169
1
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 119 publications
(185 citation statements)
references
References 153 publications
(210 reference statements)
13
169
1
2
Order By: Relevance
“…1A and B to previously published surface water structure spectra of other salts reveals some interesting differences. SFG spectra of aqueous sodium halide (12,13), ammonium and sodium sulfate (13), and divalent-cation nitrate salt solutions (12) reveal enhancements in the 3; 400 cm −1 region, although the aqueous ammonium chloride salt spectrum (13) showed enhancement at 3; 300 cm −1 as is observed here for MgCl 2 . Also different than observed in Fig.…”
Section: Resultsmentioning
confidence: 60%
See 1 more Smart Citation
“…1A and B to previously published surface water structure spectra of other salts reveals some interesting differences. SFG spectra of aqueous sodium halide (12,13), ammonium and sodium sulfate (13), and divalent-cation nitrate salt solutions (12) reveal enhancements in the 3; 400 cm −1 region, although the aqueous ammonium chloride salt spectrum (13) showed enhancement at 3; 300 cm −1 as is observed here for MgCl 2 . Also different than observed in Fig.…”
Section: Resultsmentioning
confidence: 60%
“…Before MgCl 2 addition, the spectrum of neat water reveals a broad continuum that spans from 3,000 to 3; 600 cm −1 and is assigned to the OH stretching modes of hydrogen-bonded water molecules. The assignments within this continuum are controversial and still under discussion (12); however, as the frequency of the OH stretching modes increases, the strength of the hydrogen bonds between water molecules decreases (12,13). This spectral region is also affected by coupling (14) and the collective nature of the vibrations (13).…”
Section: Resultsmentioning
confidence: 99%
“…Using deuterated and normal water, Allen and coworkers [Ma et al, 2007;Allen et al, 2009] showed that with increasing surface coverage of a phospholipid monolayer, the OD (or OH) dangling bond peak at ∼2735 cm −1 (3710 cm −1 ) does not simply disappear but is broadened and slightly red shifted due to an increased integration into the surface water network and/or confinement and perturbation imposed by the monolayer molecules. Wavenumbers of 2700 cm −1 and 3625 cm −1 have been reported for a densely covered H 2 O and D 2 O surface, respectively.…”
Section: Role Of Confined Watermentioning
confidence: 99%
“…[29][30][31][32][33][34][35][36][37][38][39][40] In particular, this technique has been applied to the in situ investigation of biomolecules, including peptides, [41][42][43][44][45][46][47][48][49][50][51][52] proteins, and DNA. [75][76][77][78][79] Previous work from our lab has demonstrated the ability of SFG spectroscopy to detect substrate modifications through a layer of adherent, fixed cells 80 and through living, nonadherent cells.…”
Section: Introductionmentioning
confidence: 99%